2020
DOI: 10.3389/fpsyg.2020.00728
|View full text |Cite
|
Sign up to set email alerts
|

Does the MRI/fMRI Procedure Itself Confound the Results of Meditation Research? An Evaluation of Subjective and Neurophysiological Measures of TM Practitioners in a Simulated MRI Environment

Abstract: Travis et al. Does MRI Confound Meditation Results? generally between sitting and simMRI, with some significant exceptions. In conclusion, these data indicate that the fMRI procedure itself (high dB noise; lying down) strongly influences subjective and neurophysiological responses during meditation practice, and may therefore confound the interpretation of results from fMRI studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The noise aspect is particularly troublesome for studying self-transcendence because it can be difficult to get into this state when a giant, loud machine is distracting the participant. A study with transcendental meditators showed that the noise from fMRI strongly influenced both subjective and neurophysiological responses during meditation practice, calling into question the fMRI results (Travis et al, 2020 ). There is no agreed-upon average value for fMRI reliability.…”
Section: Results: Research/evaluation Methods For Investigating Sementioning
confidence: 99%
“…The noise aspect is particularly troublesome for studying self-transcendence because it can be difficult to get into this state when a giant, loud machine is distracting the participant. A study with transcendental meditators showed that the noise from fMRI strongly influenced both subjective and neurophysiological responses during meditation practice, calling into question the fMRI results (Travis et al, 2020 ). There is no agreed-upon average value for fMRI reliability.…”
Section: Results: Research/evaluation Methods For Investigating Sementioning
confidence: 99%
“…These techniques either need a nonferromagnet environment or quiet operation space, which brings difficulties to patient scanning using traditional brain imaging techniques, such as fMRI. 44,154…”
Section: Resultsmentioning
confidence: 99%
“…These techniques either need a nonferromagnet environment or quiet operation space, which brings difficulties to patient scanning using traditional brain imaging techniques, such as fMRI. 44,154 Also, with a balanced temporal and spatial resolution, fNIRS combined with the AI algorithms provide potential means to detect patients' pain in real-time objectively. 37,54,119 fNIRS-AI-based pain detection originates from the concept of braincomputer interface.…”
Section: Future Directions For Functional Near-infrared Spectroscopy ...mentioning
confidence: 99%
“…However, the diversity across sites did seem to provide some internal replications to support the robustness of the findings, which followed a generally consistent pattern between cohorts. Finally, biometric data were not included in this analysis, although the use of such measures, particularly those identified in prior research on the health benefits of contemplative practices, such as markers of immune system function [ 20 , 86 ], salivary cortisol, heart rate, heart rate variability [ 87 ], blood pressure [ 36 ], electroencephalogram (EEG) [ 88 ], and MRI and fMRI [ 89 ], would strengthen future investigations.…”
Section: Discussionmentioning
confidence: 99%